The Influence of Electronic Word of Mouth and Social Media Marketing on Brand Image and Purchase Intention of E-Commerce Cosmetic Products in Medan City - Sjukun, Sjukun; Yulius, Yudi (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Electronic word of mouth (E-WOM) and Social Media Marketing are widely used by consumers to explore information about a product. Information obtained from various sources on the internet will affect consumer perceptions of brand image, risk and encourage consumer purchase intention. This study aims to examine the effect of electronic word of mouth, and social media marketing variables on purchase intention with brand image as an intervening variable. This study used a purposive sampling technique on 260 respondents. The study was conducted on all Indonesian citizens in Medan who are interested in buying and using cosmetics through e-commerce and already have income. The method used is the Structural Equation Model with AMOS 24.0 Software. The results of this study indicate that electronic word of mouth has a positive and significant effect on brand image and purchase intention, and social media marketing has a positive effect on brand image and purchase intention and is significant on brand image but not significant on purchase intention. Meanwhile, brand image has a positive and significant effect on purchase intention.